Kebijakan Penyelenggaraan Pendidikan Inklusi di Lembaga Pendidikan - Daimah, Daimah; Nahri , Aisyah Chorijatun (PT. Student RIhlah Indonesia, 2025)
Inclusion education is an innovative and strategi educational approach to expand access to education for all children with special needs including children with disabilities. the inclusion school's founders are required to provide accessibility for students with disabilities and advice to have specialized professionals in handling the crew. policies that in writing do not necessarily teraktualisasi with optimal, due to the many obstacles in the field. the more concern that is, in practice implementation still colored by ignorance of various parties, so exploitation, bully, until discrimination still continue to exist among student with disable.